RANCANG BANGUNG SISTEM INFORMASI GEOGRAFIS PENENTUAN LOKASI POTENSI SUMBER DAYA ALAM DENGAN METODE PROFIL MATCHING (STUDI KASUS : KABUPATEN KUBU RAYA) - Maylindri, Rizki Hertia (JUSTIN (Jurnal Sistem dan Teknologi Informasi), 2015)
Abstract - Natural Resources is one of the factors which are crucial to developing the potential of the region. The development of natural resources should be one of the priorities for regional development. Therefore, research is needed to support and maximize the development of the area of natural resources. The potential development of natural resources is essentially determined by the nature of the physical environment with the parameters determining the potential land based on several indicators. The purpose of this research is to design and build a system for land use of natural resources by applying the Profile Matching method, so as to provide information about a potential priority natural resources, as well as the types of natural resources appropriate for the area. Profile Matching itself is an important concept in decision-making based on ranking. Profile Matching produce information in the form of a value and that value will be used in the comparison of the value of the existing indicators. So the end result of managing spatial data systems and tabular areas of natural resources and their types of natural resources potential in Kubu Raya which is displayed in the form of maps (spatial data) in a geographic information system. Based on analysis of the system, it is known that the indicator most influence in determining the location of natural resources is an indicator of soil pH, fertility and moisture content for this type of agricultural natural resources. For the type of fishery resources, the indicator which greatly affects is water pH, water temperature, dissolved oxygen and salinity. As for the types of plantation natural resources, the indicator that most affect is the texture of the soil, peat thickness and slope, thus ranking the scores can be seen and it can be seen that the district that has the most priority village natural resources is subdistrict Sungai Raya, Sungai Kakap, Batu Ampar, dan Sungai Ambawang.